2005
DOI: 10.1016/j.visres.2005.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Seeing motion in depth using inter-ocular velocity differences

Abstract: An object moving in depth produces retinal images that change in position over time by different amounts in the two eyes. This allows stereoscopic perception of motion in depth to be based on either one or both of two different visual signals: inter-ocular velocity differences, and binocular disparity change over time. Disparity change over time can produce the perception of motion in depth. However, demonstrating the same for inter-ocular velocity differences has proved elusive because of the difficulty of is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
21
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 18 publications
1
21
0
Order By: Relevance
“…18 -20 S3D viewing often entails tracking a visual object through space and depth, and binocular disparity provides critical visual cues for detecting motion in depth. 21,22 As such, stereoscopic viewing likely affords greater motion perception than 2D viewing and, hence, induces greater motion sickness symptoms due to a heightened conflict between vision and other senses.…”
mentioning
confidence: 99%
“…18 -20 S3D viewing often entails tracking a visual object through space and depth, and binocular disparity provides critical visual cues for detecting motion in depth. 21,22 As such, stereoscopic viewing likely affords greater motion perception than 2D viewing and, hence, induces greater motion sickness symptoms due to a heightened conflict between vision and other senses.…”
mentioning
confidence: 99%
“…This idea has been controversial. Fernandez and Farell (2005) showed that adapting to frontoparallel motion improved motion-in-depth direction discrimination, consistent with a role for interocular velocity differences in motion-in-depth perception. However, Harris et al (1998) found that targets moving in the z-axis did not pop out among stationary distractors, and concluded that the visual system is not sensitive to interocular motion differences.…”
Section: Introductionmentioning
confidence: 53%
“…In addition to the changes in binocular disparity that result from these opposite retinal motions, visual percepts of 3D motion are in part determined by a mechanism that extracts interocular velocity differences (IOVDs) per se. Although there is an increasing body of evidence suggesting a strong and unique contribution of IOVDs (Brooks, 2002a(Brooks, , 2002bBrooks & Stone, 2004Czuba, Rokers, Huk, & Cormack, 2010;Fernandez & Farell, 2005;Rokers, Cormack, & Huk, 2008;Shioiri, Kakehi, Tashiro, & Yaguchi, 2009;Shioiri, Nakajima, Kakehi, & Yaguchi, 2008;Shioiri, Saisho, & Yaguchi, 2000), it is unclear how motion signals used to make this interocular comparison fit into the known visual hierarchy (Regan & Gray, 2009). We investigated whether the IOVD mechanism operated upon early stages of motion processing typically ascribed to primary visual cortex (V1), or on later stages of processing that extract the motions of patterns, which is typically ascribed to extrastriate areas like the middle temporal area (MT) and related motion processing structures (Khawaja, Tsui, & Pack, 2009;Movshon, Adelson, Gizzi, & Newsome, 1985;Perrone & Thiele, 2002;Simoncelli & Heeger, 1998).…”
Section: Introductionmentioning
confidence: 99%